Two pharmacological epoxyeicosatrienoic acid-enhancing therapies are effectively antihypertensive and reduce the severity of ischemic arrhythmias in rats with angiotensin II-dependent hypertension - Červenka, Luděk; Husková, Zuzana; Kopkan, Libor; Kikerlová, Soňa; Sedláková, Lenka; Vaňourková, Zdenka; Alánová, Petra; Kolář, František; Hammock, Bruce D; Hwang, Sung H; Imig, John D; Falck, John R; et al. (Journal of hypertension, 2018)
OBJECTIVE: We examined the effects of treatment with soluble epoxide hydrolase inhibitor (sEHi) and epoxyeicosatrienoic acids (EETs) analogue (EET-A), given alone or combined, on blood pressure (BP) and ischemia/reperfusion myocardial injury in rats with angiotensin II (ANG II)-dependent hypertension. METHODS: Ren-2 transgenic rats (TGR) were used as a model of ANG II-dependent hypertension and Hannover Sprague-Dawley rats served as controls. Rats were treated for 14 days with sEHi or EET-A and BP was measured by radiotelemetry. Albuminuria, cardiac hypertrophy and concentrations of ANG II and EETs were determined. Separate groups were subjected to acute myocardial ischemia/reperfusion injury and the infarct size and ventricular arrhythmias were determined. RESULTS: Treatment of TGR with sEHi and EET-A, given alone or combined, decreased BP to a similar degree, reduced albuminuria and cardiac hypertrophy to similar extent; only treatment regimens including sEHi increased myocardial and renal tissue concentrations of EETs. sEHi and EET-A, given alone or combined, suppressed kidney ANG II levels in TGR. Remarkably, infarct size did not significantly differ between TGR and Hannover Sprague-Dawley rats, but the incidence of ischemia-induced ventricular fibrillations was higher in TGR. Application of sEHi and EET-A given alone and combined sEHi and EET-A treatment were all equally effective in reducing life-threatening ventricular fibrillation in TGR. CONCLUSION: The findings indicate that chronic treatment with either sEHi or EET-A exerts distinct antihypertensive and antiarrhythmic actions in our ANG II-dependent model of hypertension whereas combined administration of sEHi and EET-A does not provide additive antihypertensive or cardioprotective effects.
Keywords: Angiotensin II; potkani transgenní; kyseliny arachidonové; albuminurie; antihypertenziva; angiotensin II; hypertenze; potkani Sprague-Dawley; Albuminuria; srdeční arytmie; Hypertension; Arrhythmias, Cardiac; Rats, Transgenic; krysa rodu Rattus; Animals; krevní tlak; zvířata; Rats; Antihypertensive Agents; Blood Pressure; Arachidonic Acids; Rats, Sprague-Dawley